Will College Pay Off?: A Guide to the Most Important Financial Decision You’ll Ever Make - Hala, Nicole (Radical Teacher, 2016)
Will College Pay Off?: A Guide to the Most Important Financial Decision You’ll Ever Make (PublicAffairs, 2015) by Peter Cappelli, Reviewed by Nicole Hala.